PENGARUH KEPUASAN KERJA, LINGKUNGAN KERJA NON FISIK, DAN PENGEMBANGAN KARIR TERHADAP KINERJA KINERJA ANGGOATA DITRESKRIMUM POLDA SULTRA - Yusri Yusri; Murdjani Kamaluddin; Hayat Yusuf (Pascasarjana Universitas Halu Oleo, 2023)
The purpose of this study was to examine and explain the effect of job satisfaction on the performance of members of the Directorate of Criminal Investigation at the Southeast Sulawesi Regional Police, the effect of a non-physical work environment on the performance of members of the Directorate of Criminal Investigation at the Regional Police of Southeast Sulawesi and the effect of career development on the performance of members of the Directorate of Criminal Investigation at the Regional Police of Southeast Sulawesi. This research approach is a survey with an explanatory research design. Data collection is done by using an instrument in the form of a questionnaire. The population of this study were all members of the Southeast Sulawesi Regional Police's Criminal Investigation Unit, totaling 53 people. The analytical tools used in testing the hypothesis are descriptive analysis and inferential analysis of Multiple Linear Regression by using the software package SPSS Version 24.0.The results of this study are job satisfaction has a positive and significant effect on the performance of the Ditreskimum Police of the Southeast Sulawesi Police, the non-physical work environment has a positive and significant effect on the performance of the Ditreskimum Police of the Southeast Sulawesi Police and Career development has a positive and significant effect on the performance of the members of the Ditreskimum Police of the Southeast Sulawesi Police